ANALISIS REGRESI MULTINOMIAL UNTUK PEMODELAN FAKTOR PENYEBAB KEKERASAN DALAM RUMAH TANGGA - Novitasari, Eggi; Sofro, A'yunin (MATHunesa: Jurnal Ilmiah Matematika, 2023)
Domestic violence is an act committed against a person, which results in suffering and also physical, mental, sexual, and domestic neglect which includes the threat of committing acts, coercion, and unlawful deprivation of independence within the scope of the household. This study aims to analyze the model to determine the factors that influence domestic violence. Factors that are suspected to be influential are age, education level of the victim, place of occurrence, gender of the perpetrator, citizenship status, type of relationship between the perpetrator and the victim, family income, number of family dependents. The method used is the multinomial regression method, which is one of the data analysis methods that looks for the relationship between polychotomous response variables with a nominal scale. The data in this study used data obtained from the Office of Women and Children Empowerment in 2021. The results show that age and number of family dependents are factors that have a significant effect on domestic violence. Keywords: Domestic Violence, Multinomial Regression